Utilization Of Communication Technology And Media On The Embodiment Of Creativity Development In Society - Delvia Fikri Br Tarigan (International Journal of Cultural and Social Science, 2020)
As time goes by and technology is increasingly sophisticated, peoplemust always learn new things continuously, not only byunderstanding that, people must be good at creating something newand building creativity so that they can take advantage of Technologyand Communication Media in this new era . The purpose of thisjournal is the purpose of this research, namely 1) Describe what is aCommunication Media 2) How to use it to develop creativity. Themethod used is this research is a descriptive study with a qualitativeapproach.